The Influence of Influencer Marketing on the Purchase Decision of Elizabeth Bag Products among Lampung Students - Mega Julianti; Widi Astuti; Juni Suryanadi; Edi Purwandoko; Hendri Ardianto (LPPM STIAB Jinarakkhita Lampung, 2023)
Influencer marketing is a marketing strategy by carrying out sales promotions by someone who has influence (influencer) in influencing consumers to make purchasing decisions for Elizabeth bag products among students. In the ever-growing digital era, the role of influencers in marketing strategies has become an important factor in influencing consumer purchasing decisions. This research aims to reveal the influence of influencers in marketing strategies on purchasing decisions for Elizabeth brand bag products among students. Elizabeth is a bag brand that has long been known in the fashion industry. Marketing strategies through influencers have become an integral part of efforts to reach the student market segment. The research method used in this research is a survey method, with data collection carried out through questionnaires distributed to students from various universities. The collected student data was analyzed using regression techniques to determine the extent to which the role of influencers had an impact on purchasing decisions for Elizabeth bag products. The results of this research show that the role of influencers in marketing strategies has the influence that the use of influencers in marketing strategies has been successful in communicating brand and product values to their target market.